Living in truth, beauty, and goodness values and virtues. - Wattles, Jeffrey H. (Eugene : Cascade Books, 2016)
Truth, beauty, and goodness are more than traditional ideas--they are living realities bearing dynamic potentials for a future we can help create. As we grow, these supreme values increasingly guide our thinking, feeling, and doing. No matter what your philosophical, religious, or spiritual orientation may be, having a philosophy of living centered on these ideals will enhance your understanding and integration. Seasoned by the author's experience in leading thousands of students through experiential projects, Living in Truth, Beauty, and Goodness contains all the essential ingredients to help you develop your own personal philosophy. Your guides are Darwin, Socrates, Jesus, Bach, and other world-class pioneers whose strengths and insights can inspire you to develop a resilient and virtuous character. As you explore truths in science, philosophy, and spiritual experience; beauty in nature and the arts; and goodness in morality and character, you will be encouraged to transplant what is proposed here into the garden of your own concepts and then creatively to put the emerging meanings and values into practice. -- back cover.
Keywords: Virtues; Virtues; RELIGION / Christian Theology / Ethics; Electronic books